An alkaline earth metal modified iron-zinc-potassium catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202611296138.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的目的就是为了克服上述现有技术存在的缺陷而提供一种碱土金属改性铁锌钾催化剂及其制备方法和应用,以解决现有铁基催化剂在长期二氧化碳加氢过程中表面活性物种易氧化、难以长期保持的问题
(1)本发明采用共沉淀法使碱土金属离子进入铁锌羟基碳酸盐前驱体晶格形成结构性掺杂,碱土金属占据尖晶石晶格的八面体位,实现了碱土金属与铁锌物种的紧密结构耦合。该制备方法工艺简单、条件易于控制,有利于碱土金属与铁锌物种形成紧密相互作用。本发明的结构性引入方式能够更有效地调控铁锌物种在活化及二氧化碳加氢过程中的结构演变,充分发挥碱土金属的结构调控作用。
Smart Images

Figure CN122999294A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of carbon dioxide resource utilization and iron-based catalyst technology, and in particular to an alkaline earth metal modified iron-zinc-potassium catalyst, its preparation method and application. Background Technology
[0002] As a major greenhouse gas, the efficient conversion and resource utilization of carbon dioxide are of great significance for achieving carbon resource recycling and low-carbon chemical processes. α-olefins are important basic chemical raw materials and organic synthesis intermediates, widely used in the production of polyolefins, synthetic lubricants, surfactants, and other products. Therefore, the direct synthesis of α-olefins from carbon dioxide and hydrogen can achieve both carbon dioxide resource utilization and the production of high-value-added chemical products, showing promising application prospects.
[0003] Iron-based catalysts are widely used in the hydrogenation of carbon dioxide to hydrocarbons due to their abundant raw material sources, low cost, and high catalytic activity, while also exhibiting activity in reverse water-gas shift reactions and Fischer-Tropsch synthesis. Chinese patent document CN106031871A discloses an iron-based catalyst for the hydrogenation of CO2 to produce low-carbon olefins. By controlling the chemical state of iron species and the synergistic effect between iron and potassium, high selectivity for low-carbon olefins is achieved; however, the long-term operational stability of the prepared catalyst needs further improvement. Chinese patent document CN108144617A further discloses an iron-based catalyst for the hydrogenation of carbon dioxide to α-olefins and its preparation and application methods. By optimizing the combination of iron species and promoters, high selectivity for α-olefins is achieved, but the problem of catalyst activity decline during the reaction still exists. During the reaction, iron species typically undergo a dynamic transformation from oxides to carbides, with iron carbides being the main active species for carbon chain growth and olefin formation. Therefore, regulating the composition of iron species and their in-situ dynamic structural evolution during the reaction is an important way to improve the performance of iron-based catalysts in the hydrogenation of carbon dioxide.
[0004] However, iron-based catalysts generally suffer from insufficient long-term stability during the reaction process, which is one of the important factors restricting their industrial application. During the reaction, active iron carbides are easily oxidized and deactivated by weak oxidizing substances in the reaction environment. Simultaneously, phase transitions of iron species, particle structure reconstruction, and changes in the active interface can further affect the stable existence of iron carbides, leading to a decrease in catalytic activity. To address this, Chinese patent document CN116920892A discloses a highly stable Fischer-Tropsch synthesis iron-based catalyst, attempting to improve the catalyst's operational stability through a multi-component promoter system. However, achieving long-term stable operation of over 400 hours while maintaining both carbon dioxide conversion activity and α-olefin selectivity remains a technical challenge. Therefore, how to suppress the oxidation and unfavorable structural evolution of active iron carbides during the reaction process and improve the long-term stability of iron-based catalysts is a problem that urgently needs to be solved in the carbon dioxide hydrogenation to α-olefins technology.
[0005] To address the aforementioned issues, existing research primarily focuses on improving the stability of iron-based catalysts through active phase regulation and catalyst surface structure control. On one hand, by introducing alkali metals, transition metals, or other metal promoters, the electronic structure, reduction and carburizing behavior of iron species, as well as the interactions between active species and other components, can be altered, thereby improving the catalyst's activity, selectivity, and stability. Chinese patent document CN117427670A discloses an iron-zinc-potassium catalyst for the hydrogenation of CO2 to linear α-olefins and its preparation method. Through the synergistic effect of iron and zinc and the potassium promoter, high selectivity for linear α-olefins is achieved. However, the catalyst described in this patent still mainly relies on the electronic regulation effect of the alkali metal (potassium), and maintaining the iron carbide active phase during long-term operation remains a challenge. On the other hand, constructing surface and interface structures with certain hydrophobic properties to reduce water accumulation near active iron species has also been used to weaken the oxidizing effect of water on iron carbides. Chinese patent document CN115845859A discloses a modified iron-based catalyst for the synthesis of α-olefins via carbon dioxide hydrogenation. Surface modification improves the catalyst's stability under CO2 hydrogenation conditions. However, single surface hydrophobic modulation is difficult to maintain effectively in the long term under complex multi-component reaction environments with high temperature and pressure, and the degradation of catalyst activity over time remains a prominent issue. Furthermore, iron-based catalysts undergo continuous dynamic structural evolution in complex reaction environments with high temperature, high pressure, and the simultaneous presence of multiple components such as carbon dioxide, carbon monoxide, hydrogen, and water. Single electronic modulation or surface hydrophobic modulation often fails to simultaneously achieve both the formation of active iron carbides and long-term stability.
[0006] Alkaline earth metals possess high thermal stability, and their oxide surfaces typically contain abundant alkaline sites, exhibiting strong adsorption capacity for carbon dioxide. Simultaneously, alkaline earth metals such as magnesium, calcium, and strontium can alter the dispersion state, phase evolution process, and surface adsorption properties of iron species, thereby affecting the formation and stability of iron carbides. However, a unified understanding of the specific roles of alkaline earth metals in iron-based carbon dioxide hydrogenation catalysts is currently lacking. Some studies suggest that alkaline earth metals can inhibit the oxidation of iron carbides by weak oxidizing substances such as carbon dioxide and water, thus improving the stability of iron carbides; other studies have found that carbonate species formed by alkaline earth metals during the reaction process can adversely affect catalytic performance. Therefore, the effect of alkaline earth metals on iron-based catalysts is not simply a direct promotion or stabilization of iron carbides; its actual effect is closely related to the catalyst composition and the state in which the alkaline earth metals exist. Consequently, a clear and engineering-ready technical solution is still lacking regarding the mechanisms by which alkaline earth metals act in iron-based catalytic systems and how they affect long-term stability. Summary of the Invention
[0007] The purpose of this invention is to overcome the defects of the prior art by providing an alkaline earth metal modified iron-zinc-potassium catalyst, its preparation method, and its application, so as to solve the problem that surface active species of existing iron-based catalysts are easily oxidized and difficult to maintain for a long time during long-term carbon dioxide hydrogenation.
[0008] In the conceptualization process of this invention, it was considered necessary to fully utilize the good thermal stability, surface alkalinity, and structural regulation capabilities of alkaline earth metals, and combine them with other promoters that can promote the formation and stabilization of iron species. By rationally designing the composition and preparation method of multi-component iron-based catalysts, the structural evolution of iron species in the carbon dioxide hydrogenation reaction process can be regulated. While ensuring high carbon dioxide conversion activity and α-olefin formation capacity, the oxidation resistance of active iron carbides can be improved, thereby obtaining an iron-based carbon dioxide hydrogenation catalyst with high activity, high α-olefin selectivity, and long-term stability. This provides a new catalytic material and technical solution for the efficient resource utilization of carbon dioxide to produce high-value-added α-olefins.
[0009] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a method for preparing an alkaline earth metal-modified iron-zinc-potassium catalyst, wherein alkaline earth metal ions are incorporated into the lattice of an iron-zinc hydroxycarbonate precursor to form structural doping via a co-precipitation method, specifically including the following steps: Step 1: Dissolve iron salt, zinc salt, and alkaline earth metal salt in water and stir to form a uniform and transparent mixed metal salt solution A, wherein the molar ratio of iron ions to zinc ions is (1.5~3) / 1, and the molar ratio of alkaline earth metal ions to iron ions is (0.01~1.0) / 1; dissolve alkali metal carbonate and alkali metal hydroxide in water to form a composite precipitant solution B; Step 2: Under heating and stirring conditions, solution B is added dropwise to solution A to carry out a coprecipitation reaction. The pH of the reaction system is controlled at 9.5~10.5. Then, the mixture is aged, washed, filtered and dried to obtain a solid precipitate. Step 3: The solid obtained in Step 2 is calcined for the first time in a static air atmosphere. After cooling, an alkaline earth metal modified iron-zinc composite metal oxide is obtained. The composite metal oxide has a spinel structure as the main crystal phase, with alkaline earth metals occupying octahedral positions in the spinel lattice. No characteristic diffraction peaks of independent alkaline earth metal species appear in the X-ray diffraction pattern. Step 4: Impregnate the composite metal oxide obtained in Step 3 with potassium carbonate solution in equal volume, dry it, and then calcine it a second time in a static air atmosphere. After cooling, the alkaline earth metal modified iron-zinc-potassium catalyst is obtained.
[0010] More preferably, the molar ratio of iron ions to zinc ions is 2:1.
[0011] Further, in step one, the iron salt is at least one hydrate of ferric nitrate, ferric sulfate, or ferric chloride; the zinc salt is at least one hydrate of zinc nitrate, zinc sulfate, or zinc chloride; the alkaline earth metal is at least one of magnesium, calcium, strontium, or barium; and the alkaline earth metal salt is at least one hydrate of alkaline earth metal nitrate, sulfate, or chloride. The alkali metal carbonate is at least one of lithium carbonate, sodium carbonate, or potassium carbonate, and the alkali metal hydroxide is at least one of lithium hydroxide, sodium hydroxide, or potassium hydroxide.
[0012] Furthermore, the concentration of alkali metal ions in the composite precipitant solution B is 2-5 mol / L. -1 ; In step two, the heating and stirring temperature is 25~90°C, and the stirring speed is 400~800 r / min. -1 The aging time is 2 to 6 hours.
[0013] Furthermore, in step four, each 1.0g of the composite metal oxide is impregnated with an equal volume of impregnation solution containing 0.015~0.020g of potassium carbonate.
[0014] Furthermore, in step three, the temperature of the first calcination treatment is 400~800°C, and the time is 2~6 hours; In step four, the temperature of the second calcination treatment is 400~800°C, and the time is 1~4 hours.
[0015] A second aspect of the present invention provides an alkaline earth metal modified iron-zinc-potassium catalyst, which is prepared by the above-described preparation method; The alkaline earth metal modified iron-zinc-potassium catalyst has an iron-zinc spinel structure as the main crystal phase, and the alkaline earth metal occupies the octahedral position in the spinel lattice in a structural doping manner. No characteristic diffraction peaks of independent alkaline earth metal species appear in the X-ray diffraction pattern. The molar ratio of iron to zinc in the alkaline earth metal modified iron-zinc-potassium catalyst is (1.5~3) / 1, and the alkaline earth metal accounts for 1%~10% of the total mass of the catalyst.
[0016] Furthermore, after activation by a mixture of carbon monoxide and hydrogen and a carbon dioxide hydrogenation reaction, the catalyst forms the following stable interfacial structure: (1) The main phase of iron carbide is Fe5C2, and the characteristic diffraction peaks of Fe7C3 do not appear in the X-ray diffraction pattern; (2) ZnO and Fe5C2 are in close contact to form the Fe5C2-ZnO interface, and the alkaline earth metal is highly dispersed in the form of carbonate at the Fe5C2-ZnO interface.
[0017] Furthermore, the catalyst is transformed in situ into an iron carbide-zinc oxide interface structure after the carbon dioxide hydrogenation reaction, with the iron carbide main phase being Fe5C2 and the alkaline earth metal being highly dispersed in the form of carbonate at the Fe5C2-ZnO interface. Compared with iron-zinc-potassium catalysts without alkaline earth metal structural modification, the catalyst exhibited higher oxidation consumption temperatures in both carbon dioxide and water vapor atmospheres during temperature-programmed oxidation experiments, indicating a significant improvement in the antioxidant capacity of iron carbides.
[0018] Furthermore, the alkaline earth metal is magnesium, and magnesium accounts for 2% to 5% of the total mass of the catalyst; In the fresh catalyst, magnesium exists in an amorphous or highly dispersed state in the iron-zinc spinel lattice. As the magnesium content increases, the diffraction peaks of the spinel structure in the X-ray diffraction pattern tend to be complete, indicating that the structural introduction of magnesium promotes the ordering of the spinel lattice.
[0019] A third aspect of this invention provides the application of the alkaline earth metal-modified iron-zinc-potassium catalyst described above in the hydrogenation of carbon dioxide to α-olefins. During the reaction, the catalyst forms an in-situ Fe5C2-ZnO interface structure, with the alkaline earth metal highly dispersed in the form of carbonates at the Fe5C2-ZnO interface. By physically preventing direct contact between weak oxidizing agents (carbon dioxide, water) and active iron carbides, the oxidative deactivation of iron carbides is inhibited, achieving long-term stable catalysis for the hydrogenation of carbon dioxide to α-olefins. The specific application process includes: (1) The catalyst is activated in a mixed atmosphere of carbon monoxide and hydrogen at an activation temperature of 300-400°C, an activation pressure of 0.1-1.0 MPa, and a space velocity of 8000-18000 mL g. -1 h-1 Under these conditions, activation was performed in a fixed-bed tubular reactor for 4–8 hours; (2) Switch to a mixed atmosphere of carbon dioxide and hydrogen, and react at a temperature of 300~370°C, a pressure of 1~2MPa, and a space velocity of 10000~18000 mL g. -1 h -1 The carbon dioxide hydrogenation reaction is carried out in a fixed-bed tubular reactor under the following conditions; the molar ratio of hydrogen to carbon dioxide in the mixed gas is 2~4. (3) During continuous operation, the carbon dioxide conversion rate is maintained above 37%, the α-olefin selectivity is maintained above 47%, and the continuous stable operation time is not less than 400 hours.
[0020] Compared with the prior art, the beneficial effects of the present invention in the embodiments of the present invention are as follows: (1) This invention employs a co-precipitation method to introduce alkaline earth metal ions into the lattice of the iron-zinc hydroxycarbonate precursor to form structural doping. The alkaline earth metal occupies the octahedral sites of the spinel lattice, achieving a tight structural coupling between the alkaline earth metal and the iron-zinc species. This preparation method is simple and the conditions are easy to control, which is conducive to the formation of a tight interaction between the alkaline earth metal and the iron-zinc species. The structural introduction method of this invention can more effectively regulate the structural evolution of the iron-zinc species during activation and carbon dioxide hydrogenation, giving full play to the structural regulation role of the alkaline earth metal.
[0021] (2) This invention regulates the phase evolution of iron species by introducing alkaline earth metal structures in synergy with iron-zinc bimetallic compounds, which is beneficial for the formation and maintenance of a stable iron carbide-zinc oxide interface structure during the reaction. This interface structure can improve the iron carbide's resistance to oxidation by weak oxidizing substances such as carbon dioxide and water, slow down the transformation of active iron carbides into iron oxides, and thus effectively inhibit catalyst deactivation caused by oxidation of active species and unfavorable structural evolution during long-term reactions. The catalyst of this invention maintains high carbon dioxide conversion activity and α-olefin selectivity during long-term carbon dioxide hydrogenation reactions, and has good long-term operational stability and industrial application potential. Attached Figure Description
[0022] Figure 1 This is a flowchart of the preparation method of magnesium-modified iron-zinc-potassium catalyst according to an embodiment of the present invention; Figure 2 The image shows the XRD pattern of the magnesium-modified iron-zinc-potassium catalyst before reaction in an embodiment of the present invention. Figure 3 The image shows the XRD pattern of the magnesium-modified iron-zinc-potassium catalyst after reaction in an embodiment of the present invention. Figure 4 This is an EDS mapping diagram of the magnesium-modified iron-zinc-potassium catalyst after reaction in an embodiment of the present invention; Figure 5 This is an XPS image of Fe 2p after the reaction of the magnesium-modified iron-zinc-potassium catalyst in an embodiment of the present invention; Figure 6 This is a performance graph showing the change in carbon dioxide conversion rate over time for the magnesium-modified iron-zinc-potassium catalyst according to an embodiment of the present invention. Figure 7 This is a performance graph showing the change in α-olefin selectivity over time for the magnesium-modified iron-zinc-potassium catalyst according to an embodiment of the present invention. Figure 8 The XRD patterns of zinc- and magnesium-free modified iron-potassium catalyst in Comparative Example 3 of this invention before and after reaction are shown. Figure 9 This is a graph showing the long-cycle carbon dioxide hydrogenation performance of the magnesium-modified iron-zinc-potassium catalyst in an embodiment of the present invention. Figure 10 The figure shows the experimental results of temperature-programmed oxidation of magnesium-modified iron-zinc-potassium catalyst under carbon dioxide atmosphere in an embodiment of the present invention. Figure 11 The figure shows the experimental results of temperature-programmed oxidation of magnesium-modified iron-zinc-potassium catalyst in a water atmosphere according to an embodiment of the present invention. Detailed Implementation
[0023] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Any preparation methods, materials, structures, or compositional ratios not explicitly described in this technical solution are considered common technical features disclosed in the prior art.
[0024] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to more clearly illustrate the technical solutions of the present invention and should not be used to limit the scope of protection of the present invention. Specific conditions not specified in the embodiments are performed according to conventional conditions or conditions recommended by the manufacturer; reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0025] This embodiment provides an alkaline earth metal-modified iron-zinc-potassium catalyst and its preparation method, utilizing a structural introduction method to incorporate alkaline earth metal elements to modify the structure of the iron-zinc bimetallic catalyst. Please refer to [link to previous document]. Figure 1 It includes the following steps: S1: Coprecipitation reaction Iron, zinc, and alkaline earth metal salts are dissolved together in an aqueous phase and stirred at room temperature to form a homogeneous and transparent aqueous solution A of the mixed metal salts. Alkali metal carbonates and alkali metal hydroxides are dissolved together in deionized water to form a composite precipitant solution B. Solution B is slowly added dropwise to solution A while continuously heating and stirring at a temperature of 25-90℃ and a stirring speed of 400-800 rpm. -1The pH of the mixed salt solution is controlled to be constant at around 10 (pH=10±0.5), followed by precipitation and aging for 2-6 hours to form a suspension containing the precipitate. The iron salt is at least one hydrate of ferric nitrate, ferric sulfate, or ferric chloride; the zinc salt is at least one hydrate of zinc nitrate, zinc sulfate, or zinc chloride; the alkaline earth metal is at least one of magnesium, calcium, strontium, or barium; the alkaline earth metal salt is at least one hydrate of an alkaline earth metal nitrate, sulfate, or chloride; the alkali metal carbonate is at least one of lithium carbonate, sodium carbonate, or potassium carbonate; and the alkali metal hydroxide is at least one of lithium hydroxide, sodium hydroxide, or potassium hydroxide. In the mixed metal salt solution A, the concentration of iron ions is 0.33-0.9 mol / L. -1 The concentration of zinc ions was 0.17-0.45 mol / L. -1 The concentration of alkaline earth metal ions is 0.0075-0.45 mol / L. -1 The concentration of alkali metal ions in composite precipitant solution B is 2-5 mol / L. -1 .
[0026] S2: First calcination The cooled suspension was filtered to separate the precipitate, and the separated precipitate was washed with deionized water until the pH of the washing solution reached 7.0. The resulting precipitate was dried in an oven for 12 hours at a temperature of 60-80℃. Subsequently, the dried solid was calcined in static air at a temperature of 400-800℃ for 2-6 hours. The calcined solid was ground into a uniform powder to obtain alkaline earth metal modified iron-zinc composite metal oxide.
[0027] S3: Equal volume impregnation Potassium carbonate was weighed out at a ratio of 0.01785g potassium carbonate per 1.0g of the aforementioned composite metal oxide and dissolved in deionized water to form an impregnation solution. The impregnation solution was added dropwise to the composite metal oxide and stirred thoroughly, and then dried in an oven at 60-80℃ for 12 hours.
[0028] S4: Second calcination The dried solid was calcined in static air at a temperature of 400-800℃ for 1-4 hours. The calcined solid was then ground into a uniform powder to obtain an alkaline earth metal modified iron-zinc-potassium catalyst.
[0029] This invention also provides the application of an alkaline earth metal modified iron-zinc-potassium catalyst in the hydrogenation of carbon dioxide to prepare α-olefins.
[0030] The specific process is as follows: The alkaline earth metal modified iron-zinc-potassium catalyst is first activated in a mixed atmosphere of carbon monoxide and hydrogen at an activation temperature of 300-400℃, an activation pressure of 0.1-1.0MPa, and a space velocity of 8000-18000mL g. -1 h -1 Activation was performed in a reactor for 4-8 hours under specific conditions, followed by reaction in a mixed atmosphere of carbon dioxide and hydrogen at a reaction temperature of 200-400℃, a reaction pressure of 1-3MPa, and a space velocity of 8000-18000 mL g. -1 h -1 The carbon dioxide hydrogenation reaction is carried out in the reactor under certain conditions; in this embodiment, the reactor is a fixed-bed tubular reactor.
[0031] This invention prepares a series of magnesium-modified iron-zinc-potassium catalysts with different magnesium contents through a co-precipitation-equal-volume impregnation process, and systematically characterizes their physicochemical structure and catalytic performance. Comparative examples with different components and preparation methods are used to fully verify the excellent effects of the technical solution of this invention.
[0032] Example 1 According to the molar ratio of iron to zinc ions in the metal salt solution being 2:1, 0.02 mol of ferric nitrate and 0.01 mol of zinc nitrate were weighed out, and 0.19 g of magnesium nitrate was added. The mixture was placed in a glass beaker, and 60 mL of deionized water was added. The mixture was stirred at room temperature to form a homogeneous and transparent iron-zinc-magnesium mixed salt solution A. A certain amount of potassium carbonate and potassium hydroxide were weighed out and dissolved in 60 mL of deionized water to obtain a composite precipitant solution B, in which the molar ratio of carbonate ions to iron ions was 2, and the molar ratio of hydroxide ions to metal ions was 1.6.
[0033] Heating temperature 80℃, stirring speed 600 r / min -1 Under these conditions, at 1.0 mL / min -1 Solution B was added dropwise to solution A at a constant rate, while maintaining the pH of the mixed salt solution at 10 ± 0.5. After the addition was complete, the solution was allowed to stand at 80°C for 4 hours to age, resulting in a suspension containing the precipitate.
[0034] The above suspension was filtered and separated. The resulting precipitate was washed repeatedly with deionized water until the pH of the washing solution dropped to 7.0. The washed precipitate was dried at 80 °C for 12 hours, and then calcined at 500 °C for 4 hours in static air. The calcined solid was ground into a uniform powder to obtain an iron-zinc-magnesium composite oxide.
[0035] Weigh 1.0 g of the above composite oxide, dissolve 0.01785 g of potassium carbonate in an appropriate amount of deionized water, and impregnate with an equal volume. After thorough stirring, dry at 80 °C for 12 hours. The dried solid is then calcined in static air at 500 °C for 2 hours, cooled, and ground into a uniform powder to obtain a fresh magnesium-modified iron-zinc-potassium catalyst. The magnesium content was determined to be 1.3 wt% by ICP-OES, and the resulting catalyst is denoted as 1.3MgFeZnK.
[0036] Example 2 The amount of magnesium nitrate added was adjusted to 0.50 g, and the remaining preparation steps were the same as in Example 1. The magnesium element mass fraction was determined to be 3.6 wt% by ICP-OES, and the resulting catalyst was denoted as 3.6MgFeZnK.
[0037] Example 3 The amount of magnesium nitrate added was adjusted to 1.35 g, and the remaining preparation steps were the same as in Example 1. The magnesium element mass fraction was determined to be 9.0 wt% by ICP-OES, and the resulting catalyst was denoted as 9.0MgFeZnK.
[0038] Comparative Example 1 Without adding magnesium nitrate, the remaining preparation steps are the same as in Example 1, and the resulting catalyst is denoted as FeZnK.
[0039] Comparative Example 2 After completing the co-precipitation of iron, zinc and magnesium and the first calcination according to Example 2, without equal-volume impregnation and a second calcination, the resulting catalyst is denoted as 3.6MgFeZn.
[0040] Comparative Example 3 Zinc nitrate was not added, and the amount of magnesium nitrate added was adjusted to 0.064 g. The remaining preparation steps were the same as in Example 1. The magnesium element mass fraction was determined to be 3.6 wt% by ICP-OES, and the resulting catalyst was denoted as 3.6MgFeK.
[0041] Comparative Example 4 MgO was physically mixed with the FeZnK catalyst obtained in Comparative Example 1, wherein the mass of Mg element accounted for 3.6 wt% of the catalyst mass, and the resulting catalyst was denoted as MgO-FeZnK.
[0042] Verification Example 1 The physicochemical properties of magnesium-modified iron-zinc-potassium catalysts are characterized in the attached figure.
[0043] Figure 2 This is the XRD pattern of the magnesium-modified iron-zinc-potassium catalyst of this invention before reaction. As can be seen from the figure, the catalyst before reaction is dominated by iron-zinc spinel, and the spinel structure gradually becomes more complete with increasing magnesium content. No characteristic peaks of magnesium species were observed, indicating that magnesium species exist in an amorphous or highly dispersed form.
[0044] Figure 3 This is the XRD pattern of the magnesium-modified iron-zinc-potassium catalyst of this invention after reaction. As can be seen from the figure, the catalyst after reaction is mainly composed of iron carbides, and no characteristic peaks of iron-oxygen species were observed. Magnesium species exist in the form of magnesium carbonate. After the introduction of magnesium, the iron carbides in the catalyst are transformed from a mixture of Fe7C3 and Fe5C2 into pure phase Fe5C2, indicating that magnesium induces the formation of different iron carbides by regulating the adsorption behavior on the catalyst surface.
[0045] Figure 4 This is an EDS mapping diagram of the magnesium-modified iron-zinc-potassium catalyst of this invention after the reaction. As can be seen from the diagram, the iron and zinc species in the catalyst are in close contact and bound together. Figure 3 The results indicate that the catalyst forms an Fe5C2-ZnO interface structure after the reaction. Magnesium species are distributed in a highly dispersed form on the Fe5C2 surface and the Fe5C2-ZnO interface.
[0046] Figure 5 This is an XPS image of the Fe 2p region after the reaction of the magnesium-modified iron-zinc-potassium catalyst of this invention. The image shows that all catalysts exhibit varying degrees of surface oxidation after the reaction. The magnesium-modified iron-zinc-magnesium catalyst retains more iron carbides after the reaction, demonstrating that this catalyst has superior oxidation resistance.
[0047] Catalyst performance evaluation experiment 100 mg of catalyst was weighed and loaded into a fixed-bed tubular reactor with an inner diameter of 6 mm and a length of 400 mm. During the activation stage, a mixture of 5% CO / 5% H2 / 90% N2 gas was introduced into the reactor, with a space velocity set to 15000 mL g / L. -1 h -1 and at 2℃ min -1 The mixture was heated to 350°C at a rising rate and activated at atmospheric pressure for 5 hours. It was then cooled to 150°C, and the reaction gas was switched to 20% CO2 / 60% H2 / 20% N2, with a space velocity set to 15000 mL·g⁻¹. -1 ·h -1 The pressure was increased to 1.5 MPa, and then increased at 2 °C for 1 minute. -1 The temperature was increased to 330°C and the reaction was carried out at a rate of 100°C for 100 hours.
[0048] The gaseous products generated during the reaction were cooled in a 15 °C cold trap and analyzed by online gas chromatography. The liquid phase C5-C collected in the cold trap was analyzed. 20 Hydrocarbon products were analyzed using gas chromatography-mass spectrometry (GC-MS). The results after 100 hours of reaction are shown in Table 1.
[0049] Table 1 Comparison of the performance of different catalysts in carbon dioxide hydrogenation Figure 6 This is a performance graph showing the change in carbon dioxide conversion rate over time for the magnesium-modified iron-zinc-potassium catalyst of this invention.
[0050] Figure 7 This is a graph showing the performance of the magnesium-modified iron-zinc-potassium catalyst of the present invention as a function of time for α-olefin selectivity.
[0051] Combination Figure 6 , Figure 7 As can be seen from the data in Table 1: (1) The magnesium-modified iron-zinc-potassium catalysts prepared in Examples 1-3 of this invention achieved a carbon dioxide conversion rate of over 37% and an α-olefin selectivity of over 47% in a 100-hour carbon dioxide hydrogenation performance test, demonstrating excellent catalytic activity and long-term stability.
[0052] (2) Among them, Example 2 (3.6MgFeZnK) showed the best effect, with a carbon dioxide conversion rate of about 40% and an α-olefin selectivity of 49.3%. The catalyst structure induction period was shorter than that of Example 3 (9.0MgFeZnK), indicating that the magnesium content of 3.6wt% had the strongest effect on the structural modification of the iron-zinc-potassium catalyst.
[0053] (3) Comparing with Comparative Example 1, it can be seen that when no magnesium is introduced to modify the catalyst, its carbon dioxide conversion rate and α-olefin selectivity continue to decrease as the carbon dioxide hydrogenation reaction proceeds, which proves the key role of magnesium modification.
[0054] (4) Comparing with Comparative Example 2, it can be seen that when potassium is not introduced by impregnation of equal volume, the selectivity of the catalyst for α-olefins decreases significantly, proving that potassium is a key component for promoting the formation of α-olefins.
[0055] (5) Comparison with Comparative Example 3 shows that the zinc-magnesium-free modified iron-potassium catalyst (3.6MgFeK) has lower activity. From Figure 8 The reaction revealed a distinct Fe3O4 characteristic peak in the catalyst. This indicates that magnesium alone is insufficient to produce a stabilizing effect, and the synergistic effect of iron and zinc is a necessary condition for achieving high activity and long-term stability.
[0056] (6) Compared with Comparative Example 4, the physical mixture of MgO and Comparative Example 1 (FeZnK) did not show better catalytic performance and long-term stability, indicating that the effect of the present invention comes from the structural introduction of magnesium in the iron-zinc-potassium catalyst, rather than simple physical contact.
[0057] Long-term performance testing of catalysts for carbon dioxide hydrogenation Under the same conditions as the catalyst performance evaluation experiment, the reaction time was extended to 400 hours. Results were obtained from... Figure 9As can be seen, the 3.6MgFeZnK catalyst maintained excellent catalytic performance during the 400-hour long-term performance test. After 400 hours of reaction, the carbon dioxide conversion rate remained at 40%, and the olefin selectivity still reached 48.4%. These results fully demonstrate that the catalyst of this invention possesses good catalytic activity and long-term stability in carbon dioxide hydrogenation, and has the potential for industrial application.
[0058] Temperature-programmed oxidation experiment Weigh an appropriate amount of the reaction catalyst and load it into the reactor, then add it at a rate of 25 mL / min. -1 Introduce 60% CO2 / Ar or H2O / Ar. After the gas flow stabilizes, increase the temperature at 10 °C for 1 minute. -1 The temperature was increased to 800°C at a certain rate, and mass spectrometry was used to detect the CO2 (m / z = 44) or CO (m / z = 28) signals in the exhaust gas during the heating process.
[0059] Figure 10 This is a graph showing the results of a temperature-programmed oxidation experiment of the magnesium-modified iron-zinc-potassium catalyst of this invention under a carbon dioxide atmosphere. As can be seen from the graph, the magnesium-modified catalyst exhibits a higher carbon dioxide consumption peak, indicating that the catalyst is less susceptible to oxidation by carbon dioxide.
[0060] Figure 11 This is a graph showing the experimental results of the magnesium-modified iron-zinc-potassium catalyst of this invention under a programmed temperature rise oxidation in a water atmosphere. As can be seen from the graph, the magnesium-modified catalyst exhibits a higher water consumption peak, indicating that the catalyst is less susceptible to oxidation by water.
[0061] Combination Figure 5 The catalyst retained more active iron carbides on its surface after the reaction, which fully demonstrates that the catalyst of the present invention has better antioxidant capacity in the carbon dioxide hydrogenation reaction.
[0062] In summary, this invention utilizes the synergistic effect of alkaline earth metal structural doping and iron-zinc bimetallic synthesis to achieve a pure-phase Fe5C2 catalyst and construct a stable Fe5C2-ZnO interface structure after the reaction. This interface structure enhances the resistance of iron carbides to oxidation by carbon dioxide and water. After the reaction, magnesium species are highly dispersed in the form of magnesium carbonate at the Fe5C2-ZnO interface, preventing weak oxidizing agents in the reaction environment from contacting the iron carbides. The catalyst of this invention was tested at 330 °C, 1.5 MPa, and a space velocity of 15000 mL g / L. -1 h -1 Under continuous operation for 400 hours, the carbon dioxide conversion rate remained above 37% and the α-olefin selectivity remained above 47%, demonstrating good long-term operational stability and industrial application potential.
[0063] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing an alkaline earth metal modified iron-zinc-potassium catalyst, characterized in that, The structural doping of alkaline earth metal ions into the lattice of iron-zinc hydroxycarbonate precursors is achieved through co-precipitation, specifically including the following steps: Step 1: Dissolve iron salt, zinc salt, and alkaline earth metal salt in water and stir to form a uniform and transparent mixed metal salt solution A, wherein the molar ratio of iron ions to zinc ions is (1.5~3) / 1, and the molar ratio of alkaline earth metal ions to iron ions is (0.01~1.0) / 1; dissolve alkali metal carbonate and alkali metal hydroxide in water to form a composite precipitant solution B; Step 2: Under heating and stirring conditions, solution B is added dropwise to solution A to carry out a coprecipitation reaction. The pH of the reaction system is controlled at 9.5~10.
5. Then, the mixture is aged, washed, filtered and dried to obtain a solid precipitate. Step 3: The solid obtained in Step 2 is calcined for the first time in a static air atmosphere. After cooling, an alkaline earth metal modified iron-zinc composite metal oxide is obtained. The composite metal oxide has a spinel structure as the main crystal phase, with alkaline earth metals occupying octahedral positions in the spinel lattice. No characteristic diffraction peaks of independent alkaline earth metal species appear in the X-ray diffraction pattern. Step 4: Impregnate the composite metal oxide obtained in Step 3 with potassium carbonate solution in equal volume, dry it, and then calcine it a second time in a static air atmosphere. After cooling, the alkaline earth metal modified iron-zinc-potassium catalyst is obtained.
2. The preparation method of the alkaline earth metal modified iron-zinc-potassium catalyst according to claim 1, characterized in that, In step one, the iron salt is at least one hydrate of ferric nitrate, ferric sulfate, or ferric chloride; the zinc salt is at least one hydrate of zinc nitrate, zinc sulfate, or zinc chloride; the alkaline earth metal is at least one of magnesium, calcium, strontium, or barium; and the alkaline earth metal salt is at least one hydrate of alkaline earth metal nitrate, sulfate, or chloride. The alkali metal carbonate is at least one of lithium carbonate, sodium carbonate, or potassium carbonate, and the alkali metal hydroxide is at least one of lithium hydroxide, sodium hydroxide, or potassium hydroxide.
3. The preparation method of the alkaline earth metal modified iron-zinc-potassium catalyst according to claim 1, characterized in that, The concentration of alkali metal ions in the composite precipitant solution B is 2-5 mol / L. -1 ; In step two, the heating and stirring temperature is 25~90°C, and the stirring speed is 400~800 r / min. -1 The aging time is 2 to 6 hours.
4. The preparation method of the alkaline earth metal modified iron-zinc-potassium catalyst according to claim 1, characterized in that, In step four, each 1.0g of the composite metal oxide is impregnated with an equal volume of impregnation solution containing 0.015~0.020g of potassium carbonate.
5. The method for preparing the alkaline earth metal modified iron-zinc-potassium catalyst according to claim 1, characterized in that, In step three, the temperature of the first calcination treatment is 400~800°C, and the time is 2~6 hours; In step four, the temperature of the second calcination treatment is 400~800°C, and the time is 1~4 hours.
6. An alkaline earth metal modified iron-zinc-potassium catalyst, characterized in that, Prepared by the preparation method according to any one of claims 1 to 5; The alkaline earth metal modified iron-zinc-potassium catalyst has an iron-zinc spinel structure as the main crystal phase, and the alkaline earth metal occupies the octahedral position in the spinel lattice in a structural doping manner. No characteristic diffraction peaks of independent alkaline earth metal species appear in the X-ray diffraction pattern. The molar ratio of iron to zinc in the alkaline earth metal modified iron-zinc-potassium catalyst is (1.5~3) / 1, and the alkaline earth metal accounts for 1%~10% of the total mass of the catalyst.
7. The alkaline earth metal modified iron-zinc-potassium catalyst according to claim 6, characterized in that, After activation by a mixture of carbon monoxide and hydrogen and followed by a carbon dioxide hydrogenation reaction, the catalyst forms the following stable interfacial structure: (1) The main phase of iron carbide is Fe5C2, and the characteristic diffraction peaks of Fe7C3 do not appear in the X-ray diffraction pattern; (2) ZnO and Fe5C2 are in close contact to form the Fe5C2-ZnO interface, and the alkaline earth metal is highly dispersed in the form of carbonate at the Fe5C2-ZnO interface.
8. The alkaline earth metal modified iron-zinc-potassium catalyst according to claim 6, characterized in that, The catalyst is transformed in situ into an iron carbide-zinc oxide interface structure after the carbon dioxide hydrogenation reaction. The main phase of the iron carbide is Fe5C2, and the alkaline earth metal is highly dispersed in the form of carbonate at the Fe5C2-ZnO interface. Compared with iron-zinc-potassium catalysts without alkaline earth metal structural modification, the catalyst exhibited higher oxidation consumption temperatures in both carbon dioxide and water vapor atmospheres during temperature-programmed oxidation experiments, indicating a significant improvement in the antioxidant capacity of iron carbides.
9. The alkaline earth metal modified iron-zinc-potassium catalyst according to claim 6, characterized in that, The alkaline earth metal is magnesium, and magnesium accounts for 2% to 5% of the total mass of the catalyst. In fresh catalysts, magnesium exists in an amorphous or highly dispersed state in the iron-zinc spinel lattice, and as the magnesium content increases, the spinel structure characteristic diffraction peaks in the X-ray diffraction pattern tend to be complete.
10. The application of the alkaline earth metal modified iron-zinc-potassium catalyst as described in claim 6 in the hydrogenation of carbon dioxide to prepare α-olefins, characterized in that, The catalyst forms an in-situ Fe5C2-ZnO interface structure during the reaction. Alkaline earth metals are highly dispersed at the Fe5C2-ZnO interface in the form of carbonates. By physically preventing direct contact between weak oxidizing substances and active iron carbides, the oxidative deactivation of iron carbides is inhibited, achieving long-term stable catalysis for the hydrogenation of carbon dioxide to α-olefins. Specific application processes include: (1) The catalyst is activated in a mixed atmosphere of carbon monoxide and hydrogen at an activation temperature of 300-400°C, an activation pressure of 0.1-1.0 MPa, and a space velocity of 8000-18000 mL g. -1 h -1 Under these conditions, activation was performed in a fixed-bed tubular reactor for 4–8 hours; (2) Switch to a mixed atmosphere of carbon dioxide and hydrogen, and react at a temperature of 300~370°C, a pressure of 1~2MPa, and a space velocity of 10000~18000 mL g. -1 h -1 The carbon dioxide hydrogenation reaction is carried out in a fixed-bed tubular reactor under the following conditions; the molar ratio of hydrogen to carbon dioxide in the mixed gas is 2~4. (3) During continuous operation, the carbon dioxide conversion rate is maintained above 37%, the α-olefin selectivity is maintained above 47%, and the continuous stable operation time is not less than 400 hours.
Citation Information
Patent Citations
Iron-based catalyst for low-carbon olefin production through CO2 hydrogenation, and preparation and applications thereof
CN106031871A
Preparation of iron-based catalyst for preparing alpha-alkene from carbon dioxide through hydrogenation, catalyst and application
CN108144617A
Modified iron-based catalyst for synthesizing alpha-olefin through hydrogenation of carbon dioxide and preparation method of modified iron-based catalyst
CN115845859A
High-stability Fischer-Tropsch synthesis iron-based catalyst and application thereof
CN116920892A
Catalyst for preparing linear alpha olefin through CO2 hydrogenation, and preparation method and application thereof
CN117427670A
